2008
DOI: 10.1038/gt.2008.31
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific gene modification by oligodeoxynucleotides in mouse bone marrow-derived mesenchymal stem cells

Abstract: Synthetic oligodeoxynucleotides (ODNs) had been employed in gene modification and represent an alternative approach to 'cure' genetic disorders caused by mutations. To test the ability of ODN-mediated gene repair in bone marrow-derived mesenchymal stem cells (MSCs), we established MSCs cell lines with stably integrated mutant neomycin resistance and enhanced green fluorescent protein reporter genes. The established cultures showed morphologically homogenous population with phenotypic and functional features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Primary bone marrow-derived MSCs were isolated from newborn C57BL/6 wild-type mice as described previously (17). Immunodepletion was carried out using mouse lineage depletion kit (Miltenyi Biotec, Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary bone marrow-derived MSCs were isolated from newborn C57BL/6 wild-type mice as described previously (17). Immunodepletion was carried out using mouse lineage depletion kit (Miltenyi Biotec, Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Receptor expression in primary MSC cultures was determined via FACS using fluorescent-labeled antibodies generated against Ccr3, Ccr4, Ccr5, Ccr6, Ccr7, Ccr9, Ccr10, Cxcr2, Cxcr3, Cxcr4, Cxcr7 (BioLegend, San Diego, CA) as described previously (17). Cells labeled with FITC-, PE-, PerCp/Cy5.5- or Alexa Fluor-647-conjugated antibodies were analyzed with BD FACSCalibur flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The homogeneous phenomenon of drug metabolic isoenzymes may play a major role in providing physiological regulation to avoid acute rejection [2], [4], [9]. In a recent bone marrow stem cell study, direct DNA sequencing confirmed that phenotype changes were caused by mutations [11]. In our previous study [4], all recipients underwent sequential graft liver biopsies, and DNA sequencing analysis showed that all of the final liver CYP2C19 genotypes of the recipients depended on those of the donors, but were not related to the original characteristic genotype of the recipients after LDLT.…”
Section: Discussionmentioning
confidence: 99%
“…First, delivery of ODNs or nucleases in cells maintained in culture it is easier to accomplish as it can rely on both chemical as well as physical methods of delivery. For instance, the use of chemical-based reagents such as Lipofectamine™ 2000, Fugene® HD and other of transfection reagents currently in the market, as well as electroporation devices such as Amaxa Nucleofector™ and Neon® Electroporation System have proven to be effective in delivering naked DNA, including ssODNs as well as plasmids encoding nucleases into muscle progenitor cells, SCs, and ESCs (Bertoni and Rando, 2002; Bertoni et al, 2003, 2005; Dekker et al, 2003, 2006; Pierce et al, 2003; Aarts et al, 2006; Flagler et al, 2008; Kayali et al, 2010; Corti et al, 2012; Fontes and Lakshmipathy, 2013). Additionally, viral vectors can be used to express nucleases in cases where chemical and electroporation methods pose a challenge.…”
Section: Future Of Gene Editing Strategies In Muscle Stem Cellsmentioning
confidence: 99%